THE QUR’AN AND THE READING WITCHCRAFT: STUDY ON THE USE OF QUR’AN VERSES IN THE SICCIN 1 FILM - Halimah, Nur (Universitas Nurul Jadid, 2021)
This paper presents the form of the living Qur’an contained in the film Siccin 1. This film is a Turkish horror film. The focal point of this research is the use of the verses of the Qur’an used by a shaman who is carrying out his act of witching someone. Departing from the author’s understanding of the verses of the Qur’an, which are multi-functional and have the performance as something that has great power as well as being a medicine for its users, intermediary for peace of life, against destructive supernatural powers, and other good things. However, in this film, it is different; the verses of the Qur’an are used as a tool to harm others. The author has two reasons that underlie the choice of this film as research material, namely, in the Siccin film, there is a living Qur’an phenomenon in the form of the use of the verses of the Qur’an in witchcraft rituals, and the Siccin film has become the consumption of many people. The author will research by analyzing and looking for synchronization between the ritual of witchcraft and the verses of the Qur’an used in the film Siccin. The author will also look at the informative and performative aspects of the verses of the Qur’an used in this film. The writer hopes that this research can find a synchronization of the use of the verses of the Qur’an in the ritual of witchcraft and can find the performance of the Qur’an in the film Siccin. Then, the author will examine the transformation of the verses of the Qur’an into mantras. Witchcraft in this film.